HOW SAFE ARE OUR ELDERS IN SOUTH DELHI? (Journal of Forensic Medicine & Toxicology, 2013)
There is common perception that the very old die of old age but the truth factor is that deaths in elder persons are full of atypical, uncertain and unnatural presntations.In this study those factors were being considered and evaluated which were responsible for that. It was found that during study period(jan2005-oct2006), out of total elderly cases(8.9% of the total autopsies),unnatural cause of death was found in 5.32% and natural cause in 3.58%of cases.The commonest age group involved was 60-65years(55.36%) and accident was found as the most common cause of death(80.36%).
Keywords: Unnatural deaths; Ageing; Suicides